If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14 = 2(4x + 5) Reorder the terms: 14 = 2(5 + 4x) 14 = (5 * 2 + 4x * 2) 14 = (10 + 8x) Solving 14 = 10 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 14 + -8x = 10 + 8x + -8x Combine like terms: 8x + -8x = 0 14 + -8x = 10 + 0 14 + -8x = 10 Add '-14' to each side of the equation. 14 + -14 + -8x = 10 + -14 Combine like terms: 14 + -14 = 0 0 + -8x = 10 + -14 -8x = 10 + -14 Combine like terms: 10 + -14 = -4 -8x = -4 Divide each side by '-8'. x = 0.5 Simplifying x = 0.5
| t=0.05p | | -26=4p-2 | | 4=12y | | 4x+8=3x+9 | | -6+5a=-106 | | -1/2x7=-11 | | 5+5-10= | | 3.2x-6.5y=17.8 | | 3(4+7x)=138 | | 4x+-3x+2=20 | | 9x^4-12x^3+x^3=0 | | 2Y=2-6x | | 15-4/(15-13)-10/2-8-(-9)^2/9(2^2)+(8-2)^2 | | 15x+(7x+3)=20 | | 3(6x-9)+3=-114 | | 9(2x+2)+7(3x-4)=-46 | | 6(2x+5)=30 | | (10y)+(1*100)=((y+1)*70) | | k-20=-19 | | 1/2x-8=14+1/2 | | 9x-2(x-5)=7(x+1)+6 | | 18x^3-60x^2+50x=0 | | 4(-x-14)=12 | | -11m=66 | | 4(-6+-.5y)+2y=-24 | | 1/3(a+4)=1/2(3-a) | | 9(2x+2)+7(-3x-4)=-42 | | 4x^2+3x-22=0 | | 3f^2-10f+8=0 | | m-5m-2m-9= | | 14k=-42 | | -12=x+(-6)+2 |